Swaziland : 2002 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Swaziland. (IMF Staff Country Reports; Country Report, 2003)
This 2002 Article IV Consultation highlights that real GDP growth for Swaziland fell from 7 3/4 percent annually during the 1980s to 3 3/4 percent during the 1990s. In 2001, growth declined further to 1.8 percent, reflecting a fall in export demand associated with the economic slowdown in South Africa, foreign disinvestment in some industries, and poor weather. Economic activity appears to have weakened further in 2002, with manufacturing output showing the effects of additional closures by foreign firms and agricultural output being affected by the drought in the region.